2014
DOI: 10.1017/s0029665114000263
|View full text |Cite
|
Sign up to set email alerts
|

The effects of substitution of dietary saturated fatty acids with either monounsaturated fatty acids or n-6 polyunsaturated fatty acids on measures of endothelial function, arterial stiffness and blood pressure: results from the DIVAS study

Abstract: Endothelial dysfunction has been recognised as an early modifiable marker in the development of atherosclerosis and risk of cardiovascular disease (CVD) (1) . A central public health strategy for the reduction of CVD includes the reduction in dietary saturated fatty acid (SFA) intake (2) . However, it remains unclear whether monounsaturated fatty acids (MUFA) or n-6 polyunsaturated fatty acids (n-6 PUFA) are the optimal fatty acids to replace dietary SFA. The aim of this study was to determine the effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that a diet high in MUFA may be a healthier alternative to a low-fat diet, as it can lower blood cholesterol levels, modulate immune function, decrease the susceptibility of LDL to oxidation, and enhance the fluidity of HDL [ 68 ]. Furthermore, including PUFA in the diet is crucial for the structure and function of membrane proteins, such as receptors, enzymes, and active transport molecules [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a diet high in MUFA may be a healthier alternative to a low-fat diet, as it can lower blood cholesterol levels, modulate immune function, decrease the susceptibility of LDL to oxidation, and enhance the fluidity of HDL [ 68 ]. Furthermore, including PUFA in the diet is crucial for the structure and function of membrane proteins, such as receptors, enzymes, and active transport molecules [ 69 ].…”
Section: Discussionmentioning
confidence: 99%